Time-dependent inflammatory factor production and NFκB activation in a rodent model of intermittent hypoxia (Swiss Medical Weekly, 2011)
OBJECTIVE: To study the systemic production of inflammatory factors and activation of transcription factor nuclear factor kappa B (NF-κB) in response to different levels of intermittent hypoxia and time. METHODS: A total of 160 male Wistar rats were divided randomly into five groups. The first three groups were exposed to 5%, 7.5% and 10% intermittent hypoxia (referred to as IH-1, IH-2, and IH-3 respectively), the fourth group were subjected to 10% sustained hypoxia (abbreviated as SH), and the control group were exposed to normal oxygen (designated SC). At the second, fourth, sixth, and eighth week, eight rats in each group were sacrificed to collect serum. Enzyme-linked immunosorbent assay (ELISA) was used to detect the serum concentration of tumour necrosis factor alpha (TNF-α), interleukin-8 (IL-8), interleukin-6 (IL-6) and interleukin-10 (IL-10). Western blot was used to detect the protein levels of the phosphorylated NF-κB P65 in the nucleus of arterial endothelial cells. RESULTS: In all three IH groups serum levels of TNF-α, IL-8 and IL-6 showed consecutive increment from onset to the 6th week under intermittent hypoxia; the levels of TNF-α and IL-8 dropped slightly on the 8th week, whereas those of IL-6 continued to increase. The levels of IL-10 decreased and reached nadir at the 6th week of intermittent hypoxia treatment. The inflammatory response was the most pronounced in the 6th week, at which time the TNF-α, IL-8 and IL-6 levels in IH groups were significantly higher than in the SC and SH group (F = 30.04, 11.77, 18.589; p